2023
DOI: 10.21203/rs.3.rs-2521595/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunotherapy Responsiveness and Risk of Relapse in Down Syndrome Regression Disorder

Abstract: Down syndrome regression disorder (DSRD) is a clinical symptom cluster consisting of neuropsychiatric regression without an identifiable cause. This study evaluated the clinical effectiveness of IVIg and evaluated clinical characteristics associated with relapse after therapy discontinuation. A prospective, multi-center, non-randomized, observational study was performed. Patients met criteria for DSRD and were treated with IVIg. All patients underwent a standardized wean off therapy after 9–12 months of treatm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Studies evaluating the long‐term use of IVIg in persons with DSRD has identified that many patients can be weaned off therapy after 12 months of infusions (Santoro, Spinazzi, et al, 2023). Although the exact mechanisms by which this is possible are being explored, the absence of abnormal neuroimaging and abnormal cerebrospinal fluid profiles are often predictive of the ability to wean off over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluating the long‐term use of IVIg in persons with DSRD has identified that many patients can be weaned off therapy after 12 months of infusions (Santoro, Spinazzi, et al, 2023). Although the exact mechanisms by which this is possible are being explored, the absence of abnormal neuroimaging and abnormal cerebrospinal fluid profiles are often predictive of the ability to wean off over time.…”
Section: Discussionmentioning
confidence: 99%
“…While these therapeutics were beneficial in individuals with DSRD, they did not treat the underlying cause of DSRD and thus required long‐term use while providing sub‐optimal efficacy. With advancements in the understanding of abnormal neurodiagnostics indicating neuroinflammation in some individuals with this condition, three large multi‐center studies have identified the clinical utility of intravenous immunoglobulin (IVIg) in the treatment of DSRD (Santoro, Baumer, et al, 2022; Santoro, Partridge, et al, 2022; Santoro, Spinazzi, et al, 2023). Importantly, IVIg has been reported to have efficacy rates of 70–90% in individuals with DSRD and is most effective when neurodiagnostic biomarkers such as abnormal neuroimaging and/or abnormal cerebrospinal fluid analysis are present (Santoro, Baumer, et al, 2022; Santoro, Partridge, et al, 2022; Santoro, Spinazzi, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis is often missed in mainstream mental health settings, causing significant delays and potentially poorer outcomes for individuals and their families. Effective treatments include treating the catatonia with lorazepam or electroconvulsive therapy, and use of immune-based therapies including intravenous immunoglobulin (Santoro et al, 2023).…”
Section: Objectives: To Describe the Diagnosis Clinical Features And ...mentioning
confidence: 99%
“…Therapeutic interventions for this condition are broad and have ranged from antipsychotics to immunotherapy [99]. A minority of individuals with DSRD may have a neuroinflammatory etiology to the disease, confirmed by the presence of abnormal neurodiagnostic studies and dramatic immunotherapy responsiveness in some patients [93,95,100,101]. While immunotherapy provides a tool to rapidly reverse this clinical syndrome, guidance on dosing and duration of therapy remains unclear.…”
Section: Neurological Disordersmentioning
confidence: 99%